A Novice Approach of Designing CMOS Based Switchable Filters for ASP Applications - Rajinder Tiwari; G R Mishra (International Journal of Electrical and Computer Engineering (IJECE), 2015)
A switchable filter can be designed and fabricated with the desired range and parameters, materials say quartz substrate for RF MEMS based applications. The mathematical modeling of the resonators using the desired characteristics of the capacitive coupled filters can be implemented with low insertion loss. In order to design this filter, one can employ a PIN diode along with a semi-lumped resonator. This PIN diode has been used so as it performs the function of electronic switching i.e. the activating and deactivating the filter circuit action without any compromise in the overall performance of the circuit. These filters circuit are designed and implemented in a way so that it can accommodate the external quality factor in order to ensure a good impedance match at each band of operation. The most dominant parameters and characteristics of the second order switchable filter realization. In this work, the author has put an effort to discuss the most desired parameters of the various switchable filters. In these filter circuits, CMOS devices has been used to design because of their well accepted features i.e. low power loss and requirement of low input signal for operation in addition to other ones. The performance of the proposed CMOS based switchable filters has been discussed with its simulated results that have been carried out by using pSpice software with 0.18 micron technology. The insertion loss of this circuit is with the acceptable limits i.e. 2.9 dB and a tenability within two desired frequencies.